EFFICACY OF BIODYNAMIC COMPOST APPLICATION ON PRODUCTION OF RICE - Singh, FATEH; KUMAR, RAVINDRA; PAL, SAMIR; KUMAR, PRAMOD (Annals of Agricultural Research, 2014)
A field experiment was conducted for six crop seasons in same layout beginning with wheat (Rabi 2001-02) at Research Station, Kalai, Aligarh of C.S. Azad University of Agriculture and Technology, Kanpur. The experiment was conducted in RBD with four replications having nine treatments. It may be concluded that use chemical fertilizers along with biodynamic compost and biofertilizer are more beneficial in improving soil fertility and productivity of rice- and biofertilizers is more beneficial in improving soil fertility and productivity of rice-wheat cropping system. In view of the information generated on the system there appears to be a vast potential of augmenting production in alluvial soil. If renewable resources are scientifically and judiciously managed, the long-term sustainability of production can inevitably be ensured. Â